Polymorphism in PLIN2 gene and its association with growth traits in Chinese native cattle. Issue 2 (3rd March 2020) - Yue, Binglin; Wu, Jiyao; Shao, Simin; Zhang, Chunlei; Fang, Xingtang; Bai, Yueyu; Qi, Xingshan; Chen, Hong
Abstract: Perilipin 2 (PLIN2) is a cytosolic protein that regulates intracellular lipid storage and mobilization. However, research reports of the relationship between PLIN2 gene and growth traits in cattle are rare. Here, five novel single nucleotide polymorphisms (SNPs)（g.3036G > C, g.3964C > T, g.6458G > T, g.6555C > T and g.8231G > A）were identified within the bovine PLIN2 gene using DNA sequencing and PCR-SSCP methods in 820 individuals from four Chinese indigenous bovine breeds. Overall, five common haplotypes were identified based on the 5 SNPs, with the most common haplotypes (GCGCG) occurring at a frequency of 69.0%. In addition, The 5 novel SNPs were associated with growth traits at 6, 12, 18 and 24 months in Nanyang population, and significant associations were found in body weight and heart girth. These results suggest that PLIN2 possibly is a strong candidate gene marker for body weight in cattle breeding program.